Evaluation of producing and marketing entire male pigs. (1st March 2016) - Backus, G.B.C.; van den Broek, E.; van der Fels, B.; Heres, L.; Immink, V.M.; Knol, E.F.; Kornelis, M.; Mathur, P.K.; van der Peet-Schwering, C.; van Riel, J.W.; Snoek, H.M; de Smet, A.; et al.
Highlights: Boar tainted meat was rated as less pleasant by consumers, indicating the need of detection as a safety net at the slaughter line. Breeding was an effective preventive measure to reduce boar taint. Human nose scores were a better predictor of consumer perception, compared to skatole levels and to androstenone levels. Farms with appropriate management, feeding and housing conditions have reduced levels of mounting and aggressive behaviour. Abstract: This paper presents the results of a research program that was aimed at evaluating: (1) sensory evaluation of meat from entire male pigs, (2) preventive measures to reduce boar taint prevalence, (3) accuracy of detection for boar taint, and (4) the relationship between farm management characteristics and levels of mounting and aggressive behaviour of boars. Using observational and experimental studies data were collected in various segments of the pork supply chain. Consumer acceptance of meat from entire male pigs was evaluated. The effectiveness of preventive measures to reduce boar taint prevalence was determined. The relationship of farm (management) characteristics with boar taint prevalence, animal behaviour, skin lesions and lameness respectively was analysed. The similarity of the rank order between consumer perception of odour and human nose scores, skatole and androstenone levels respectively was determined. Consumers evaluate meat that passed the boar taint detection test comparable to meat from gilts. Meat samples that did not pass this test were evaluated less favourable. Ranking AI boars on their genomic breeding values for low boar taint resulted in a reduction in boar taint prevalence of 40%. The skatole level is lower in boars fed via a long trough than in boars fed by a single space feeder. Few eating places, restricted feeding, a low level of amino acids in the diet, insufficient water supply of the drinking system, illness of the pigs, a suboptimal climate and fear for humans were associated with a higher level of sexual and aggressive behaviour and more skin lesions. A partly open pen wall, clean pens and pigs, wider gaps of the slats, feeding by a long trough, and feeding wet by-products were associated with less sexual and aggressive behaviour and less skin lesions. Having more than 30 animals per pen was associated with a higher probability of high boar taint prevalence levels. Hygienic conditions were associated with lower boar taint prevalence levels. Assessing similarity of the rank order comparison between consumer perception and three selected boar taint detection parameters for the consumer perception attribute odour of meat resulted in the highest Kendall's W values for the human nose scores. In conclusion, boar tainted meat was rated as less pleasant by consumers compared to meat of gilts and non-tainted boar meat, indicating the need of detection as a safety net at the slaughter line. Breeding was an effective preventive measure to reduce boar taint. Farms with appropriate management, feeding and housing conditions have reduced levels of mounting and aggressive behaviour. Human nose scores were a better predictor of the rank order of consumer perception, compared to skatole levels and to androstenone levels.